Correlations between Electrochemical Data and Results from Post-Mortem Analysis of Aged Lithium-Ion Batteries. Issue 8 (14th May 2015) - Waldmann, Thomas; Ghanbari, Niloofar; Kasper, Michael; Wohlfahrt-Mehrens, Margret
Abstract : Material degradation is an issue limiting the life-time of Lithium-ion batteries. This study conducts quantitative observations of performance and material degradation in a commercial high-power Lithium-ion battery as a function of aging time and ambient temperature. Batteries are cycled until different states-of-health (SOHs) in the range of 100% to 78% are obtained before being disassembled. Inductively coupled plasma (ICP-OES) analysis of the electrodes from cells in different SOHs reveals a linear increase in Li, P, and Mn on anodes with aging time and thus allows conclusions on the kinetics of the aging reactions. The vertical distribution of these decomposition products in the anode is investigated by glow discharge optical emission spectroscopy (GD-OES) depth profiling. Following this, the chemical data from Post-Mortem analysis are correlated to the electrochemical performance of the cells. Combining chemical data sets from aged cells in different SOHs with data from cells aged at different ambient temperature reveals an Arrhenius-like behavior of chemical changes on the anodes.